Bioactive glass-ceramic composites from the Li2O-ZrO2-SiO2 and Beta-Tricalcium-Phosphate system for bone regeneration: Evaluation of bioactivity and cytotoxicity - Natália Morelli Possolli; Henrique Borba Modolon; Daiara Floriano da Silva; Natasha Maurmann; Patricia Pranke; Elidio Angioletto; Oscar Rubem Klegues Montedo; Sabrina Arcaro (REM: International Engineering Journal, 2025)
Abstract Bioactive glass-ceramics are attractive for medicine and have been widely investigated. A growing number of studies have shown that bone tissue regeneration can be stimulated by bioactive glasses with different chemical compositions. In this way, glasses from the LZS system (Li2O-ZrO2-SiO2) have interesting mechanical, electrical, and thermal properties. However, they have not been studied for bone regeneration yet. In these materials, the presence of lithium as a bioactive ion can accelerate the deposition of hydroxyapatite, which represents bone regeneration. The bioactivity of the LZS glass-ceramic system has been proven. In this context, this research aims to investigate the bioactivity of glass-ceramic composites of the LZS system and tricalcium phosphate (TCP). To this end, the thermal properties of the raw materials were analyzed. Different compositions of LZS with TCP were prepared and thermally characterized. They were then treated at 800 °C and 900 °C and characterized in density, porosity, structure, and microstructure. The compacts were submerged in simulated body fluid (SBF) for different periods. Structural and microstructural analyses proved their bioactivity. Some samples were subjected to degradation tests by immersion in TRIS-HCl, quantifying the release of Li+ and Ca+. The cytotoxicity test was performed using glass-ceramics in direct contact with mesenchymal stem/stromal cells (SC), isolated from exfoliated human deciduous teeth. The results show that it was possible to produce bioactive glass-ceramics from LZS, as evidenced by the formation of new calcium phosphate structures, such as hydroxyapatite, on the surface of the samples after exposure to SBF. The SC viability test indicated that the materials were not cytotoxic at 0.25, 0.5, and 1.0 mg/ml. The glass-ceramic system under study is promising for medicinal applications in bone regeneration.